1997
DOI: 10.1002/(sici)1097-4644(1997)27+<35::aid-jcb8>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention by naturally occurring and synthetic agents in oral, liver, and large bowel carcinogenesis

Abstract: A number of naturally occurring compounds and several related synthetic agents were confirmed to exert chemopreventive properties against carcinogenesis in the digestive organs. Phenolic compounds, widely distributed as plant constituents, possess chemopreventive activities in tongue, liver, and large bowel of rodents. Of them, a simple phenolic protocatechuic acid seems to be a promising compound. Organosulfur compounds contained in the cruciferous vegetables and known to activate detoxifying enzymes are rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 31 publications
2
18
0
2
Order By: Relevance
“…Cy is unstable under physiological conditions and degraded to PC, even if Cy were absorbed into the circulatory system. It is known that PC has a protective potency in carcinogenesis [18]. C3G feeding is expected to improve the antioxidant capability and chemically prevent carcinogenesis in vivo.…”
Section: C3g and Its Metabolites In The Tissuementioning
confidence: 99%
“…Cy is unstable under physiological conditions and degraded to PC, even if Cy were absorbed into the circulatory system. It is known that PC has a protective potency in carcinogenesis [18]. C3G feeding is expected to improve the antioxidant capability and chemically prevent carcinogenesis in vivo.…”
Section: C3g and Its Metabolites In The Tissuementioning
confidence: 99%
“…Modulation of phase I or II enzymes, and suppression of lipid peroxidation or DNA adduct formation are one of them. 37,38) Reddy et al reported that organosulfur compounds increase glutathione S-transferase (GST) and NAD(P)H-dependent quinone reductase (NAD(P)H:QR) in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…35,36) Shin and Lin 37) have reported that curcumin inhibited TPA-induced lipid peroxidation and 8-hydroxydeoxyguanosine formation in mouse fibroblasts. Such antioxidative properties may be involved in the chemopreventive effect on esophageal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%